Theoretical Determination of Molecular Weight of AB2 Dendrimers - Abdoulhossien Massoudi; Hooshang Vahedi; Omid Louie; Sami Sajjadiffar (E-Journal of Chemistry)
The Molecular weight of any AB2 type dendrimers were calculated by suggested theoretical equation. The results were compared with the data reported by others. It was found that there are no remarkable differences between the calculated and reported data.